New perspectives on medical clowning. - Raviv, Amnon (Abingdon, Oxon ; New York, NY : Routledge, 2023)
Taking the recent coronavirus pandemic as a starting point, this book presents and analyzes new research around medical clowning in hospitals, from social media use to the impact on the hospitalized child in later life. This innovative book begins with an overview of the work of medical clowns. It discusses the idea of humor as a mechanism related to the revolution in language and human consciousness, and makes a connection between humor and anxiety, exploring how this can be mobilized to support hospitalized patients. There is extensive examination of medical clowning to strengthen coping skills and promote wellbeing in the time of Covid-19, where loneliness and isolation loomed large and anxieties were high. Subsequent chapters explore the role of medical clowning in wartime and at time of natural disasters, the experiences of children some time after their experience of hospitalization and clowning, and the role of social media and medical clowns in community building. This book is a fascinating contribution to the literature on medical clowning. It is of interest to researchers, practitioners, and lecturers in medical clowning, play in healthcare, nursing, medicine, and performance studies.
Keywords: Clowning -- Therapeutic use; Wit and humor -- Therapeutic use; MEDICAL / Allied Health Services / General; MEDICAL / Education & Training; MEDICAL / Health Care Delivery